Efficient and Compressive Hybrid Data Dissemination Model with Data Aggregation in Healthcare Applications Using WSN - Abdul Raheem, SyeD; M. Prabhakar, Dr.; C. Venugopal, Dr.; Gillela, Kumar (International Journal of Engineering and Technology, 2018)
Wireless sensor Networks (WSN) have great attention within the past years to provide the choices of flexibilities and save the value of patients and health care activities. Constant time, during disaster events, there is a developing health care area which is able to produce actual care to the patient. For the reason, equipmentâ€™s are modified to observe the patient that has great attention to enhance the efficiency and Quality value of health care. Huge amount of real-time information on the hospitals Sensors used to monitor the patient information that turns out a progressively. The medical data of a private is extremely sensitive; it is an important problem in a hospital during the transmission of this information through wireless networks. For communication the information size get reduces in data aggregation. This paper aims to reduce the traffic within the cluster so as to enhance the energy efficiency and for that purpose a hybrid data dissemination model is proposed which uses the enhanced comb needle model and compressive data sensing. Comb Needle Model is the simplest network that can be compared with proposed hybrid data dissemination model by exploitation the parameters like the ratio of packet delivery, average delay, throughput, and cost of communication and intake of energy.Â Â Â